1993
DOI: 10.2527/1993.711132x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-carnitine and soybean oil on performance and nitrogen and energy utilization by neonatal and young pigs

Abstract: A total of 64 neonatal pigs was used in an experiment to study the effect of L-carnitine and soybean oil on pig performance and N and energy utilization. Pigs were weaned at an average of 3 d of age and individually fed diets that contained dextrose, corn syrup solids, and isolated soy protein for 21 d. Two levels of soybean oil (1.18 or 12.31%) and L-carnitine (0 or 800 ppm) were used in a factorial arrangement of treatments. Diets were formulated to contain the same nutrient content per megacalorie of ME. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…However, on the basis of the results of our study, the inability of added fat to improve growth and feed conversion immediately after weaning was not altered by L-carnitine. Our findings support those of Hoffman et al (1993), who also reported that the addition of L-carnitine to soy protein-based diets did not preferentially improve performance of neonatal and young pigs fed diets containing crude soybean oil. However, in contrast to our results, Hoffman et al (1993) did not observe improvement in growth performance from added Lcarnitine.…”
Section: Discussionsupporting
confidence: 91%
“…However, on the basis of the results of our study, the inability of added fat to improve growth and feed conversion immediately after weaning was not altered by L-carnitine. Our findings support those of Hoffman et al (1993), who also reported that the addition of L-carnitine to soy protein-based diets did not preferentially improve performance of neonatal and young pigs fed diets containing crude soybean oil. However, in contrast to our results, Hoffman et al (1993) did not observe improvement in growth performance from added Lcarnitine.…”
Section: Discussionsupporting
confidence: 91%
“…Further, our results are comparable with experiments that increased carnitine supply to piglets in their first weeks of life by other ways. In piglets weaned at day 3 of age, the supplementation of the replacement diet with carnitine did not improve growth performance during the 21-day experimental period (Hoffman et al, 1993). Likewise, litters suckled by sows supplemented with carnitine during lactation, which are known to exhibit greater carnitine concentrations in milk, did not differ in their weight gains until weaning from those suckled by unsupplemented sows (Musser et al, 1999;Birkenfeld et al, 2006).…”
Section: Discussionmentioning
confidence: 80%
“…Likewise, supplementary L-carnitine did not affect live-weight gains, feed intake or egg production in laying hens (Rabie et al, 1997;Celik et al, 2004). Ineffectiveness of L-carnitine supplementation on growth was also reported in other species, such as neonatal and weaner pigs (Hoffman et al, 1993;Cho et al, 1999;Owen et al, 2001). On the contrary, supplementary L-carnitine improved growth rates and feed efficiency (Rabie and Szilagyi, 1998), increased breast or thigh meat yield, and decreased abdominal fat content (Rabie and Szilagyi, 1998;Xu et al, 2003) in broiler chickens.…”
Section: Weight Gain (G/bird)mentioning
confidence: 72%